Púrpura trombocitopênica idiopática: importância do cirurgião-dentista no diagnóstico - Simonato, Luciana Estevam; Miyahara, Glauco Issamu [UNESP]; Biasoli, Eder Ricardo [UNESP] (My University, 2010)
This paper presents a case report of a patient with idiopathic thrombocytopenic purpura (ITP) diagnosed in routine dental care. ITP is defined as a decrease in the number of circulating platelets and generally shows oral manifestations. In this light, we show that the general dental practitioner must be ready to detect ITP signs and symptoms, especially oral changes that are not of dental origin, so as to immediately prescribe the proper treatment. Without this treatment, this pathology may well be irreversible and fatal.

Esse trabalho descreve um caso de púrpura trombocitopênica idiopática (PTI) diagnosticado durante exame odontológico de rotina. A PTI é uma desordem caracterizada pela destruição anormal das plaquetas circulantes e geralmente apresenta manifestações bucais. Dessa forma, destacamos a importância de o cirurgião-dentista estar apto a reconhecer os sinais e sintomas da PTI, principalmente mudanças bucais que não têm origem dental, possibilitando tratamento imediato. Esta patologia quando não tratada, pode ser irreversível e fatal.
Keywords: Thrombocytopenic purpura idiopathic; Diagnosis; Púrpura trombocitopênica idiopática; Diagnóstico